POLSKIE PORADNIKI DYPLOMATYCZNE PRZEŁOMU XVI I XVII WIEKU WOBEC DYLEMATU “WOLA WŁADCY CZY DOBRO WSPÓLNE” - MICHAŁ NOWAKOWSKI (Pl.it, 2021)
The aim of the article is to analyse three 16th and 17th centuries Polish diplomatic manuals written by Krzysztof Warszewicki, Ławryn Piaseczyński and Stanisław Miński dealing with the dilemma ‘the will of the ruler or the common good’, also known as ‘the prince or peace’ dilemma. This problem highlights the tension between the two opposing concepts of political order in early modern Europe: absolutist and republican. The article focuses on the attitude of the aforementioned authors towards the role of the monarch and the community of the republic, as well as the relationship between the monarch and the ambassadors.